A Pan-Cancer Analysis Revealing the Dual Roles of Lysine (K)-Specific Demethylase 6B in Tumorigenesis and Immunity - Ding, Jia-Tong; Yu, Xiao-Ting; He, Jin-Hao; Chen, De-Zhi; Guo, Fei (Frontiers in Genetics, 2022)
Introduction: Epigenetic-targeted therapy has been increasingly applied in the treatment of cancers. (K)-specific demethylase 6B (KDM6B) is an epigenetic enzyme involved in the coordinated control between cellular intrinsic regulators and tissue microenvironment whereas the pan-cancer analysis of KDM6B remains unavailable. Methods: The dual roles of KDM6B in 33 cancers were investigated based on the GEO (Gene Expression Omnibus) and TCGA (The Cancer Genome Atlas) databases. TIMER2 and GEPIA2 were applied to investigate the KDM6B levels in different subtypes or stages of tumors. Besides, Human Protein Atlas database allowed us to conduct a pan-cancer study of KDM6B protein levels. GEPIA2 and Kaplan-Meier plotter were used for prognosis analysis in different cancers. Characterization of genetic modifications of the KDM6B gene was analyzed by the cBioPortal. DNA methylation levels of different KDM6B probes in different TCGA tumors were analyzed by MEXPRESS. TIMER2 was applied to determine the association of KDM6B expression and immune infiltration and DNA methyltransferases. Spearman correlation analysis was used to assess the association of KDM6B expression with TMB (tumor mutation burden) and MSI (microsatellite instability). KEGG (Kyoto encyclopedia of genes and genomes) pathway analysis and GO (Gene ontology) enrichment analysis were used to further investigate the potential mechanism of the KDM6B gene in tumor pathophysiology. Results: KDM6B was downregulated in 12 cancer types and upregulated across 4 types. In KIRC (Kidney renal clear cell carcinoma) and OV (Ovarian serous cystadenocarcinoma), KDM6B level was significantly associated with the pathological stage. High level of KDM6B was related to poor OS outcomes for THCA (Thyroid carcinoma), while low level was correlated with poor OS and DFS prognosis of KIRC. KDM6B expression level was associated with TMB, MSI, and immune cell infiltration, particularly cancer-associated fibroblasts, across various cancer types with different correlations. Furthermore, enrichment analysis revealed the relationship between H3K4 and H3K27 methylation and KDM6B function. Conclusions: Dysregulation of DNA methylase activity and methylation level of H3K4 and H3K27 may involve in the dual role of KDM6B in tumorigenesis and development. Our study offered a relatively comprehensive understanding of the KDM6B`s dual roles in cancer development and response to immunotherapy.